Oncogenic snoRNA SNORD78 fuels colorectal cancer by protecting the m 6 A reader IMP2 to enhance phospholipid metabolism - Yingqi Zhao; Xiaoyun Hu; Yalun Li; Jing Zhang; Hao Guo; Yuying Zhang; Ting Wu; Jinyu Guo; Yi Peng; Ying Che; Xianglong Zhu; Qiuchen Chen; et al. (Proceedings of the National Academy of Sciences, 2026)
Small nucleolar RNAs (snoRNAs) play crucial regulatory roles in various cancers. However, the mechanisms by which snoRNAs regulate N6-methyladenosine (m 6 A) modifications in colorectal cancer (CRC) remain unclear. This study systematically deciphered the precise interaction mechanism between SNORD78 and the m 6 A reader IMP2 in CRC. We demonstrate that SNORD78 specifically stabilizes IMP2 to activate the PIK3CD-CHKA-Kennedy pathway in an m 6 A-dependent manner, promoting endoplasmic reticulum stress (ERS) and phosphatidylcholine (PC) biosynthesis, thereby driving CRC. Conversely, the SNORD78 -targeting antisense oligonucleotide (ASO), ASO-78, effectively suppresses ERS and PC levels, inhibiting CRC progression. Mechanistically, SNORD78 , relying on the “UAAUGA” element in its C-D box region, specifically binds to the Lys221 ubiquitination site of IMP2, blocking TRIM25-mediated degradation of IMP2 and maintaining its stability. IMP2 enhanced the stability and translation of the target mRNAs PIK3CD and CHKA by recognizing their corresponding m 6 A positions, m 6 A-3208 and m 6 A-1619, respectively, to reshape the phosphatidylcholine metabolite profile in CRC cells. In terms of potential therapeutic strategies, the ASO-78 can significantly inhibit CRC cell proliferation, reduce ERS levels, and decrease phosphatidylcholine content. The combination of ASO-78 and IMP2 inhibitor IMP2-IN1, by dual blocking of the SNORD78 –IMP2 axis, exhibits an excellent proliferation-inhibiting effect in CRC organoids. This study not only reveals a mechanism by which the SNORD78 –IMP2 interaction regulates CRC occurrence and development but also provides theoretical basis for innovative therapeutic strategies for precise targeting of tumor snoRNA-m 6 A reader interactions.